Analisis Inovatif Terhadap Akad Jual Beli Syariah: Integrasi Teknologi Digital, Efisiensi Praktis, dan Prinsip ESG dalam Ekonomi Islam Kontemporer - Arlinta Prasetian Dewi; Suselo, Dedi (DPPM Universitas Pelita Bangsa, 2025)
This article discusses innovation in the implementation of Sharia-compliant sales contracts through a multidimensional approach: digital technology integration, practical efficiency analysis, and the application of sustainability principles (Environmental, Social, and Governance/ESG) in contemporary Islamic economics. This study uses a qualitative method with a desk study approach, examining six main contracts: Murabahah, Salam, Istisna', Ijarah, Wadiah, and Qard al-Hasan. The findings indicate that digitalization offers opportunities to increase transaction efficiency and transparency, but requires attention to Sharia compliance. Furthermore, the ESG approach demonstrates the alignment of Sharia values ​​with global sustainability principles. This research emphasizes the importance of collaboration between regulators, industry players, and academics in developing innovative Sharia-compliant contract models that are responsive to the challenges of the times.